2022
DOI: 10.1111/jcmm.17557
|View full text |Cite
|
Sign up to set email alerts
|

NANOG regulates epithelial–mesenchymal transition via AMPK/mTOR signalling pathway in ovarian cancer SKOV‐3 and A2780 cells

Abstract: NANOG engages with tumour initiation and metastasis by regulating the epithelial–mesenchymal transition (EMT) in epithelial ovarian cancer (EOC). However, its role in association with pAMPKα, and its clinical significance in EOC have not been elucidated even though AMPK is known to degrade NANOG in various human cancers. Hence, we investigated the role of pAMPKα and its association with NANOG as potential prognostic biomarkers in EOC. Both NANOG and pAMPKα expression were significantly overexpressed in EOCs co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…Bareiss et al documented that Sox2-expressing cells are more resistant to cell death the via apoptotic pathway caused by different chemotherapeutic agents or TRAIL [40]. Yun et al [41] demonstrated that the silencing of Nanog by siRNA caused a decreased migration activity and invasiveness of two analyzed human ovarian cancer cell lines, SKOV-3 and A2780. Furthermore, the silencing of Nanog decreased the expression of EMT markers, such as vimentin, N-cadherin, and ZEB1, and the activation of the AMPK/mTOR signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Bareiss et al documented that Sox2-expressing cells are more resistant to cell death the via apoptotic pathway caused by different chemotherapeutic agents or TRAIL [40]. Yun et al [41] demonstrated that the silencing of Nanog by siRNA caused a decreased migration activity and invasiveness of two analyzed human ovarian cancer cell lines, SKOV-3 and A2780. Furthermore, the silencing of Nanog decreased the expression of EMT markers, such as vimentin, N-cadherin, and ZEB1, and the activation of the AMPK/mTOR signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, FOXA2 has been in favor of decreasing cancer metastasis and it suppresses EMT [ 54 ]. Since molecular pathways regulating EMT mechanism have been somewhat well understood [ 55 ], studies have focused on EMT targeting in cancer therapy [ 52 ]. Decrease in N-cadherin and vimentin levels, and increase in E-cadherin levels can be observed after administration of β-elemene in inhibiting EMT in colorectal tumor [ 56 ].…”
Section: Emt Mechanism: General Aspects and Carcinogenic Functionmentioning
confidence: 99%
“…Under physiological conditions, NANOG is responsible for the self-renewal and the pluripotency of embryonic stem cells (ESCs) [ 213 ]. In ovarian cancer, it regulates self-renewal but also EMT and chemo-resistance via the STAT3 signalling pathway [ 214 ]. Yun et al [ 214 ] demonstrated a correlation between the expression of NANOG in OCSCs and a high grade and resistance to standard chemotherapy.…”
Section: Ovarian Cancer Stem Cells Markersmentioning
confidence: 99%
“…In ovarian cancer, it regulates self-renewal but also EMT and chemo-resistance via the STAT3 signalling pathway [ 214 ]. Yun et al [ 214 ] demonstrated a correlation between the expression of NANOG in OCSCs and a high grade and resistance to standard chemotherapy. Sex-determining region Y-box 2 (SOX2) plays a similar role to NANOG in the physiological state [ 215 ].…”
Section: Ovarian Cancer Stem Cells Markersmentioning
confidence: 99%